Gestión de mantenimiento y su influencia en el índice de accidentabilidad en una planta concentradora de cobre, 2016 - 2018 - Vallejo Urquiaga, Alonso Martin Alamiro (2020)
ABSTRACT The purpose of the research is Maintenance Management and its Influence on the Accident Rate Index in a Copper Concentrator Plant, 2016-2018, was carried out in the maintenance area of the Toromocho Project, located in the district of Morococha, province of Yauli, department de Junín, which was made up of 890 workers (including third-party service). The techniques used were direct observation (allowed to identify the present dangers and risks) and the documentary review (it will serve to identify the incidents and accidents that occurred) and the instruments used were the Checklist of Guidelines of the Safety and Health Management System in the Work (Supreme Decree N ° 005-2012-TR) and the indices that make up the occupational safety and health statistics (DS Nº 024-2016-EM). The diagnosis of the occupational health and safety management system for the maintenance area shows that they are in a GOOD rating, with a value of 90.08% for 2018. Maintenance management at the 2016 copper concentrator plant was determined - 2018 had average values of 1.1; 1.6 and 2.4, respectively, the values of occupational safety and health statistics showed the tendency to decrease and grow in productivity without human losses for the years 2016 to 2018. The main occupational health and safety operational controls that influence management of maintenance were: Visible Leadership Program, Carry out investigation of accidents - incidents occurred, Comply with action plans for accidents - Incidents, Perform the homologation of suppliers for maintenance, Comply with the training and training plan, Perform planned and unplanned inspections , among others that complement the strengthening of the preventive culture. The behavior of the accident rate was determined with respect to the UP TIME, showing that an inversely proportional relationship, while the accident rate decreases, the productivity increases significantly and the ratio of the indicators, index of accident rate with UP Time, under a polynomial regression model presented a correlation of 1.